Examining information literacy experience in light of activity theory and task complexity - Kamran Toroghi, Fereshteh; Sanatjoo, Azam; Tajafari, Masoumeh (Malaysian Journal of Library and Information Science, 2022)
This study aims at examining information literacy in light of activity theory and task complexity. The sample of this survey consists of 86 randomly selected university employees with simple and complex tasks. Three researcher-made questionnaires collected information concerning information literacy, relevant components of activity theory in all stages of information literacy experiences and task complexity. Regarding the components of information needs, namely, identifying information sources, searching, combining new information with prior knowledge and updating information, the analysis indicates that these components enjoyed a satisfactory level in terms of simple tasks. Analysis, evaluation, selection and implementation of information at the workplace, however, were not satisfactory among people with simple tasks. The findings showed that elements of activity theory significantly and positively impacted information needs, sources and seeking behaviour of both groups of employees; information analysis and evaluation behaviour in employees with complex tasks; information selection and summary behaviour in the group assigned to simple tasks; combining new information with prior knowledge in employees with simple tasks. These factors, too, had a significantly positive effect on the ability to update information in both groups. These factors in activity theory also had a significant positive effect on information literacy experiences in both groups; however, the effect was larger for employees assigned to simple tasks, compared to those assigned to complex tasks.